Game-Based Learning in Language Instruction: An Islamic Perspective - Hasibuan, Kalayo; Fadilah, Rosikhatul; Jannah, Satya; Nabila, Safna Khoiro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of Game-Based Learning (GBL) in language instruction from an Islamic perspective through a qualitative library research approach. The study aims to synthesize previous findings regarding the effectiveness of GBL, the integration of Islamic values in language learning, and the challenges associated with its implementation. Data were collected from 23 selected studies published between 2020 and 2025 and analyzed using thematic analysis. The findings indicate that GBL enhances learners’ motivation, engagement, communication skills, vocabulary development, and language achievement while reducing learning anxiety. The review also reveals that the integration of Islamic values such as honesty, responsibility, cooperation, respect, and discipline contributes to learners’ moral and spiritual development. Furthermore, the analysis identifies several implementation challenges, including technological limitations, teacher readiness, assessment issues, and the need for culturally appropriate learning materials. The study highlights the importance of integrating language learning objectives, game-based instructional strategies, and Islamic values to support holistic learner development. Therefore, GBL can be considered an effective pedagogical approach that promotes linguistic, social, moral, and spiritual growth in contemporary educational settings